Sex Differences in Rest-Activity Circadian Rhythm in Patients With Metabolic Syndrome - Mulè, Antonino; Bruno, Eleonora; Pasanisi, Patrizia; Galasso, Letizia; Castelli, Lucia; Caumo, Andrea; Esposito, Fabio; Roveda, Eliana; Montaruli, Angela (Frontiers in Physiology, 2021)
Rest-Activity circadian Rhythm (RAR) can be used as a marker of the circadian timing system. Recent studies investigated the relationship between irregular circadian rhythms and cardiovascular risk factors such as hypertension, obesity, dyslipidemia. These factors are related to the Metabolic Syndrome (MS), a clustering of metabolic risk factors that increases the risk of several cardiovascular and metabolic diseases. The aim of this cross-sectional analysis was to explore the RAR characteristics by actigraphy in subjects with MS, particularly in relation to sex and MS parameters, using parametric and non-parametric analyses. Distinguishing the characteristics of RAR on the basis of sex could prove useful as a tool to improve the daily level of activity and set up customized activity programs based on each person’s circadian activity profile. This study showed that females exhibit higher values than males in the Midline Estimating Statistic of Rhythm (MESOR) (243.3±20.0 vs 197.6±17.9 activity count), Amplitude (184.5±18.5 vs 144.2±17.2 activity count), which measures half of the extent of the rhythmic variation in a cycle, and the most active 10-h period (M10) (379.08±16.43 vs 295.13±12.88 activity count). All these parameters are indicative of a higher daily activity level in females. Females also had lower Intradaily Variability (IV) than males (0.75±0.03 vs 0.85±0.03 activity count), which indicates a more stable and less fragmented RAR. These preliminary data provide the first experimental evidence of a difference in RAR parameters between males and females with MS.